Lymphocyte function-associated antigen 1 (LFA-1): a surface antigen distinct from Lyt-2,3 that participates in T lymphocyte-mediated killing. - Davignon, D (1981)
Monoclonal antibodies (MAb) have been used to probe the relationship of cytolytic T lymphocyte (CTL) surface molecules to CTL function. Rat MAb to mouse CTL were generated. Twelve MAb so obtained gave preferential binding to T cells as compared to B cells, and three of these recognized previously undescribed surface polypeptides. These Mab and more broadly reactive and previously obtained MAb were tested for their ability to block CTL-mediated killing in the absence of complement. To ensure that any observed blocking was due to binding of MAb to the effector cell rather than the target cell, a xenogeneic mouse CTL anti-rat BN lymphoma target cell system was utilized (MAb and target cells both of rat origin). Of 24 MAb tested here, 21 had little or no effect on CTL function, including those to H-2, Thy-1, Lyt-1, Ly 5, Ly 6, Lgp 100, and at least six other defined antigens. We confirmed inhibition of killing with two MAb to Lyt-2,3. Another MAb, M7/14, gave profound and consistent blockade of CTL function. It was confirmed that M7/14 MAb blocks killing by binding to the mouse CTL and does not bind to the rat lymphoma target cells used for the CTL assay. The findings suggest that the antigen defined by M7/14, termed a lymphocyte function-associated antigen, LFA-1, participates in or is closely associated with the mechanism of CTL-mediated killing. LFA-1 contains two polypeptide chains of 180,000 and 95,000 Mr and is distinct from other described lymphocyte glycoproteins. LFA-1 thus represents both a previously undescribed lymphocyte surface antigen and molecular site for blockade of CTL-mediated killing.